ROLE OF VITAMIN C AS AN ADJUVANT THERAPY IN PATIENTS WITH SEVERE PNEUMONIA IN TERMS OF REDUCED HOSPITAL STAY - ZAHID, T; HAIDER, N; SAADAT, R; ZAHRA , FT; REHMAN, H; FAROOQ, A (Biological and Clinical Sciences Research Journal, 2024)
Vitamin C is well-known for its antioxidant and immune-boosting properties, which can theoretically influence respiratory infections. Numerous studies have explored the role of vitamin C in preventing and treating respiratory infections such as pneumonia in adults. However, there is limited on its effects as adjuvant treatment in pneumonia, in the pediatric population. We conducted this study to compare the effects of vitamin C vs placebo along with standard therapy, reducing the mean hospital stay duration in children with severe pneumonia. Methods: We conducted a randomized control trial over 1 year (1st September 2023 to 30th August 2024) in Children's Hospital, PIMs. We recruited 120 children aged 2 months to 60 months admitted with severe pneumonia. The patients were divided into two groups GROUP A and GROUP B by randomization using the lottery method. Group A received standard antibiotics plus 200 mg of vitamin C daily and Group B received standard antibiotics with a placebo. Duration of hospital stay, duration of fever, cough duration, days on oxygen, days to improve respiratory distress, and days to improve tachypnea were taken as outcomes Results: This study aimed to assess the clinical efficacy of Vitamin C supplementation in patients' children with severe pneumonia, focusing on its impact on hospital stay duration. Additional outcomes evaluated included the duration of fever, cough, oxygen use, respiratory distress, and tachypnea. The findings from our randomized controlled trial (RCT) revealed no statistically significant differences between the Vitamin C and placebo groups for any of these outcomes. This included hospital stay duration (p = 0.57), fever duration (p = 0.49), cough duration (p = 0.51), days on oxygen (p=0.73), days with respiratory distress (p=0.32), and duration of tachypnea (p-values= 0.93). Conclusion: Although the role of Vitamin C in immune support, its antioxidant activity and anti-inflammatory activity theoretically justify its use in pneumonia, the findings of our study conducted on children did not indicate any significant impact of Vitamin C use on the clinical progression of the disease.